2016
DOI: 10.1097/md.0000000000004238
|View full text |Cite
|
Sign up to set email alerts
|

Etiologies and prognostic factors of leukocytoclastic vasculitis with skin involvement

Abstract: In this study, outcomes of patients with leukocytoclastic vasculitis (LCV) were analyzed focusing on clinical, histopathology and laboratory findings, relapses, and survival.Data from patients with cutaneous vasculitis diagnosed between January 1, 2000, and December 31, 2010, at Dijon University Hospital (France) were retrospectively reviewed. LCV was defined as perivascular neutrophilic infiltrate, endothelial cell nuclear swelling, extravasation of red blood cells, and/or fibrin deposition in vessels. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 31 publications
5
52
2
5
Order By: Relevance
“…9,10 A causal agent or an underlying condition has been reported in 20-85 percent of the cases. 11,12,10,13 Similar to our findings, a previous study from India had found that drugs were the most common aetiological factor in vasculitis. 14 In contrast to our study, some previous studies had shown that antibiotics rather than NSAIDs were responsible for drug-induced vasculitis.…”
Section: Discussionsupporting
confidence: 87%
“…9,10 A causal agent or an underlying condition has been reported in 20-85 percent of the cases. 11,12,10,13 Similar to our findings, a previous study from India had found that drugs were the most common aetiological factor in vasculitis. 14 In contrast to our study, some previous studies had shown that antibiotics rather than NSAIDs were responsible for drug-induced vasculitis.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, it has been shown that drugs and mild infections such as upper respiratory tract infections are responsible for 25% and 10% of SoCSVV, respectively. [3,4] In our study these frequencies were a little different with more infections (33.3%) than drugs (16.7%) as causal agents of SoCSVV.…”
Section: Discussioncontrasting
confidence: 46%
“…However, other skin lesions, such as red macules, urticaria vasculitis, and ulcers, may be observed. [3,4] In our series, red macules were identified as the second most common clinical finding in patients with SoCSVV. Interestingly, in a multivariate logistic regression analysis, we identified macules as an independent factor of ulcers’ occurrence in the course of vasculitis.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In adults, the diagnosis of HSP is more difficult, especially in atypical forms. Many other diagnoses involving LCV must be ruled out, including infection, drug effects, malignancy and connective tissue disease [5] . According to the EULAR recommendations [3] , in the case of atypical forms (atypical cutaneous manifestations or incomplete forms of disease), the presence of IgA deposits (which has a sensitivity and specificity of >80%) is required.…”
Section: Discussionmentioning
confidence: 99%